2018
DOI: 10.1111/ctr.13421
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of perioperative surgical complications in pediatric kidney transplantation: A comparison of pre‐emptive and post‐dialysis recipients

Abstract: Purpose To determine whether there is a benefit to pre‐emptive kidney transplantation in reducing surgical complications in pediatric population. Methods A retrospective review of kidney transplantations in our institution from 2000 to 2015 was performed. Intra‐ and postoperative complication rates and one‐year graft survival were compared in their respective donor type groups (pre‐emptive DD vs post‐dialysis DD; pre‐emptive LD vs post‐dialysis LD). Results A total of 318 patients were identified (pre‐emptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…We observed surgical complications requiring revision in 15.4% of the cases, comparable to a recent report by Kim et al 17 Intra‐ or postoperative vascular complications (6.8%), mainly due to thrombosis were the most frequent complications observed in the immediate perioperative course and were associated with an increased rate of graft loss and thus reduced graft survival, as stated by others in the past 18‐20 . Of note, in case of early surgical revision and salvage of the graft, subsequent long‐term survival was not significantly impeded, as also reported by Gander and Soliman et al 20,21 As opposed to general assumptions and reports stating an increase of perioperative morbidity and especially thrombotic events in infants and children, we did not observe and increase in perioperative complications in young and small recipients, confirming previously published results by Gander and Weitz et al 22‐27 However, our analysis identified young donors as a significant risk factor for an increase in vascular complications as was reported by others especially in case of solitary transplants 24,28‐35 .…”
Section: Discussionsupporting
confidence: 91%
“…We observed surgical complications requiring revision in 15.4% of the cases, comparable to a recent report by Kim et al 17 Intra‐ or postoperative vascular complications (6.8%), mainly due to thrombosis were the most frequent complications observed in the immediate perioperative course and were associated with an increased rate of graft loss and thus reduced graft survival, as stated by others in the past 18‐20 . Of note, in case of early surgical revision and salvage of the graft, subsequent long‐term survival was not significantly impeded, as also reported by Gander and Soliman et al 20,21 As opposed to general assumptions and reports stating an increase of perioperative morbidity and especially thrombotic events in infants and children, we did not observe and increase in perioperative complications in young and small recipients, confirming previously published results by Gander and Weitz et al 22‐27 However, our analysis identified young donors as a significant risk factor for an increase in vascular complications as was reported by others especially in case of solitary transplants 24,28‐35 .…”
Section: Discussionsupporting
confidence: 91%
“…Butani and Perez 2 found a lower rejection rate in PKT patients compared with non-PKT patients. By contrast, Kim et al 27 found similar perioperative complication rates between PKT and non-PKT children. Our study was not able to study these clinical or surgical advantages, because of lack of data in the REIN registry.…”
Section: Discussionmentioning
confidence: 86%
“…Kết quả này cao hơn so với một số báo cáo trong nước ở bệnh nhân người lớn với 20% biến chứng chung trong nghiên cứu của Nguyễn Minh Tuấn (2020), trong số đó biến chứng mạch máu gặp trong 7/84 trường hợp [4]. Kết quả của chúng tôi cũng cho thấy tỷ lệ biến chứng cao hơn một số báo cáo ở trẻ em của tác giả Oliver tại Đức với tỷ lệ biến chứng chung sau mổ là 15,4% trong đó 6,8% là biến chứng mạch máu và 4,5% là chảy máu [5]; tương tự với các kết quả theo báo cáo của tác giả Jin Kim tại Canada [6]. Chúng tôi ghi nhận 1 trường hợp (3,3%) hẹp động mạch thận.…”
Section: Bàn Luậnunclassified